Pengaruh Kinerja Modal Intelektual Terhadap Kualitas Laba - Pratiwi, Annisa Anjani; Widiatmoko, Jacobus; Indarti, Maria Goreti Kentris (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2023)
This study aims to examine the effect of the performance of intellectual capital in the form of human capital, employed capital, and structural capital with company characteristics consisting of firm size, leverage, profitability as control variables on earnings quality. This research uses Penman's (1998) model as a measure of earnings quality, while Pulic's (1999) model as a measure of intellectual capital. Sampling used a purposive sampling method and produced 380 selected samples. The data used is secondary data taken from the annual financial reports of manufacturing companies listed on the IDX for 2019 – 2021. The results show that capital employed and structural capital have a significant positive effect on earnings quality, while human capital has no effect on earnings quality. The control variable firm size has a significant positive effect on earnings quality, while leverage and profitability have no effect on earnings quality.